Effects of palbociclib in oral squamous cell carcinoma and the role of PIK3CA in conferring resistance - Zainal, Nur Syafinaz; Lee, Bernard Kok Bang; Wong, Zheng Wei; Chin, Iuan Sheau; Yee, Pei San; Gan, Chai Phei; Mun, Kein Seong; Rahman, Zainal Ariff Abdul; Gutkind, J. Silvio; Patel, Vyomesh; Cheong, Sok Ching (Chinese Anti-cancer Association, 2019)
Objective: Lack of effective therapies remains a problem in the treatment of oral squamous cell carcinoma (OSCC), especially in patients with advanced tumors. OSCC development is driven by multiple aberrancies within the cell cycle pathway, including amplification of cyclin D1 and loss of p16. Hence, cell cycle inhibitors of the CDK4/6-cyclin D axis are appealing targets for OSCC treatment. Here, we determined the potency of palbociclib and identified genetic features that are associated with the response of palbociclib in OSCC. Methods: The effect of palbociclib was evaluated in a panel of well-characterized OSCC cell lines by cell proliferation assays and further confirmed by in vivo evaluation in xenograft models. PIK3CA-mutant isogenic cell lines were used to investigate the effect of PIK3CA mutation towards palbociclib response. Results: We demonstrated that 80% of OSCC cell lines are sensitive to palbociclib at sub-micromolar concentrations. Consistently, palbociclib was effective in controlling tumor growth in mice. We identified that palbociclib-resistant cells harbored mutations in PIK3CA. Using isogenic cell lines, we showed that PIK3CA mutant cells are less responsive to palbociclib as compared to wild-type cells with concurrent upregulation of CDK2 and cyclin El protein levels. We further demonstrated that the combination of a PI3K/mTOR inhibitor (PF-04691502) and palbociclib completely controlled tumor growth in mice. Conclusions: This study demonstrated the potency of palbociclib in OSCC models and provides a rationale for the inclusion of PIK3CA testing in the clinical evaluation of CDK4/6 inhibitors and suggests combination approaches for further clinical studies.